Efectos de la radiación ultravioleta en asfaltos colombianos - FREDY REYES; WILMAR DARIO FERNANDEZ; HERIBERTO AMADO; Joyce M. Rojas (Revista Científica, 2012)
he aim of this research was to observe the long and short term aging of two Colombian asphalts (60/70 and 80/100 from Barrancabermeja) through Rolling Thin Film Oven Test (RTFOT), RTFOT plus Ultra Violet radiation (UV) and accelerate aging by Pressure Aging Vessel (PAV) tests during two different exposure periods. Physical and Rheological properties such as penetration, ductility, softening point, viscosity with Brookfield and DSR were analyzed in all the stages. Results from both rhe- ological and physical characterization show no variation between samples analyzed by RTFOT and PAV in comparison with the oRTFOT plus UV radiation during 100 hours periods.